2009
DOI: 10.1016/j.msea.2009.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior of laser consolidated IN-625 at room and elevated temperatures

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 1 publication
2
19
1
1
Order By: Relevance
“…This work showed that pore-and crack-free depositions of these alloys could be produced. The tensile strength and the fatigue resistance at room temperature and at 650 C of IN-625 alloy produced by laser powder deposition (LPD), casting, and hot working were compared by Theriault et al 9 At room temperature the tensile strength of IN-625 prepared by LPD was higher than in the as-cast condition and slightly lower than in the wrought condition. The tensile strength decreased with increasing laser beam power, reflecting the increasing coarseness of the microstructure due to the corresponding decrease in cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…This work showed that pore-and crack-free depositions of these alloys could be produced. The tensile strength and the fatigue resistance at room temperature and at 650 C of IN-625 alloy produced by laser powder deposition (LPD), casting, and hot working were compared by Theriault et al 9 At room temperature the tensile strength of IN-625 prepared by LPD was higher than in the as-cast condition and slightly lower than in the wrought condition. The tensile strength decreased with increasing laser beam power, reflecting the increasing coarseness of the microstructure due to the corresponding decrease in cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, direct metal deposition (DMD) techniques for Inconel 625 components have attracted more and more attentions in recent years [9]. Among these techniques, the laser rapid manufacturing (LRM) for superalloy components has the most extensive applications in virtue of fine structure, better mechanical characteristics and lower part distortion [10][11][12]. Paul samples.…”
Section: Introductionmentioning
confidence: 99%
“…Results are presented in Table 5. [13]. The elevated temperature tensile properties of AA5083-H111 also indicate a significant decrease in strength at 200ºC, as presented in Table 2.…”
Section: Fatigue Lifementioning
confidence: 86%